2020
DOI: 10.1002/ajoc.202000295
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Trifluoromethylated Pyrrolidines via Cu–Catalyzed Asymmetric 1,3‐Dipolar Cycloaddition

Abstract: An efficient access to chiral pyrrolidine derivatives bearing one trifluoromethylated quaternary stereogenic centers is developed through Cu(I)/(S)-TF-BiphamPhos-catalyzed asymmetric 1,3-dipolar cycloaddition of azomethine ylides with tert-butyl 2-(trifluoromethyl)acrylate in moderate to high yields, excellent diastereoselectivities and good enantioselectivities (up to 95% yield, > 20 : 1 dr, 89% ee).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Especially, lots of drugs and bioactivated compounds including pyrrolidine motifs exhibit remarkable pharmacological activities when the pyrrolidine ring bearing a quaternary carbon at C-3 position. For example, some representative examples of pyrrolidines containing quaternary stereocenter always exhibit a broad range of important biological activities (Figure 1), such as antibacterial agent [5], anthelmintic activity (Cucurbitine) [6,7], Amitifadine as the triple reuptake inhibitors [8], RORγt inverse agonists [9] and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, lots of drugs and bioactivated compounds including pyrrolidine motifs exhibit remarkable pharmacological activities when the pyrrolidine ring bearing a quaternary carbon at C-3 position. For example, some representative examples of pyrrolidines containing quaternary stereocenter always exhibit a broad range of important biological activities (Figure 1), such as antibacterial agent [5], anthelmintic activity (Cucurbitine) [6,7], Amitifadine as the triple reuptake inhibitors [8], RORγt inverse agonists [9] and so on.…”
Section: Introductionmentioning
confidence: 99%
“…The study by Wang's group reported the utilization of metallated azomethine ylides in [3 + 2] cycloadditions with a variety of electron deficient alkenes. 16 The improved reactivity and efficient enantiocontrol from metal-bonded amino esters shed light on our new chiral imine-bonded activation method for the Mannich-type reaction of glycine ester. Herein, we wish to disclose a new co-catalytic system of 2-picolinaldehyde and a chiral Yb III complex of N , N ′-dioxides, 17 which was optimized to be efficient to catalyze the diastereo- and enantioselective Mannich/condensation cascade reaction of glycine ester with aromatic aldimines under mild conditions ( Scheme 1c ).…”
Section: Introductionmentioning
confidence: 99%
“…[1] Among them, the 32CA reaction of azomethine ylide 1 with alkene derivative 2 is an appealing alternative for the construction of regiochemically and stereochemically defined pyrrolidines 3 (Scheme 1). [2][3][4] The oxindole ring fused to the pyrrolidine system, namely, the spirooxindole pyrrolidines, requires special mention in heterocyclic chemistry owing to their compelling biological reliability (Scheme 2) since the last decade. [5][6][7][8][9][10] The anticancer, [5,6] antimalarial, [7] antileishmenic [8] and antiviral [9] properties of these heterocycles are well known with evaluated cytotoxic activity, [10] consequently inviting several synthetic approaches [11][12][13] to these biologically relevant synthons.…”
Section: Introductionmentioning
confidence: 99%